Physical Stability Test and Total Phenolic Content Determination of Spray Gel Formulation with Ethanol 70% Melinjo Leaf (Gnetum gnemon L.) Extract with Combination of Carbopol 940 and HPMC as Gelling Agent - Nelly Suryani; Vivi Anggia; Halimah Dewi; Rosa Adelina; Sabrina Dahlizar; Ofa Suzanti betha; Estu Mahanani Dhilasari; Ismiarni Komala; Yardi Saibi (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
The stability of a pharmaceutical preparation is very important in formulation to ensure product efficacy and safety. This research aims to test the physical stability and total phenolic content of a spray gel preparation made from 70% ethanol extract of melinjo leaves (Gnetum gnemon L.) with a combination of Carbopol 940 and HPMC as gelling agents. Antioxidant activity was tested using the DPPH method, while total phenolic content was measured using the Folin-Ciocalteu reagent and expressed in gallic acid equivalents (mgGAE/g). The results analysis of total phenolic content in the 70% ethanol extract of melinjo leaves showed a value of 46.237 mg GAE/g. Meanwhile, the total phenolic content in the spray gel formulation of the 70% ethanol extract of melinjo leaves was recorded at 0.88 mg GAE/g."Based on evaluation, the best formula is a combination of Carbopol and Hidroxypropyl methylCellulosa, HPMC (0.4%:0.4%), but the stability test results show physical instability. Further modifications are required to produce a physically stable formula.